2009
DOI: 10.1007/s10822-009-9263-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel target sites and an inhibitor of the dengue virus E protein

Abstract: Dengue and related flaviviruses represent a significant global health threat. The envelope glycoprotein E mediates virus attachment to a host cell and the subsequent fusion of viral and host cell membranes. The fusion process is driven by conformational changes in the E protein and is an essential step in the virus life cycle. In this study, we analyzed the pre-fusion and post-fusion structures of the dengue virus E protein to identify potential novel sites that could bind small molecules, which could interfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 49 publications
2
66
0
1
Order By: Relevance
“…Schmidt and co-workers suggested that the conformational transition from a pre-fusion arrangement to a post-fusion trimer will require removal of the ligand, imposing a barrier to completion of the fusion process. For this reason, in silico screens found potential pocket-binding compounds, that in some cases yielded active inhibitors [6063]. Thus the electrostatic interaction of R1074 in a well-defined cavity at the base of the stem region and our functional data showing its role in trimer stabilization and membrane fusion activity suggest that this cavity might be a target for small molecule fusion inhibitors.…”
Section: Resultsmentioning
confidence: 96%
“…Schmidt and co-workers suggested that the conformational transition from a pre-fusion arrangement to a post-fusion trimer will require removal of the ligand, imposing a barrier to completion of the fusion process. For this reason, in silico screens found potential pocket-binding compounds, that in some cases yielded active inhibitors [6063]. Thus the electrostatic interaction of R1074 in a well-defined cavity at the base of the stem region and our functional data showing its role in trimer stabilization and membrane fusion activity suggest that this cavity might be a target for small molecule fusion inhibitors.…”
Section: Resultsmentioning
confidence: 96%
“…Several groups have previously used in silico screening to identify small molecules that bind in a proposed “hinge region” pocket discovered in the high resolution crystal structure of soluble DENV2 E prefusion dimer crystallized with the detergent beta- octoglucoside (Modis, et al, 2003). Compounds identified in these virtual screens include, among other compounds, 2,4-disubstituted pyrimidines and quinazolines that inhibit DENV entry (Kampmann, et al, 2009; Poh, et al, 2009; Wang, et al, 2009; Yennamalli, et al, 2009; Zhou, et al, 2008). While these compounds are proposed to interact with the hinge region pocket, structural data or resistance mutations validating this as the binding site and documenting that this interaction results in inhibition of membrane fusion have been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the crystal structure of the DENV2 E protein displays a ligand-binding pocket that was occupied by a detergent molecule, n-octyl-b-D-glucoside (b-OG) [15]. This initiated several groups to identify and optimize potential inhibitors targeting this region of E protein for DENV [16,17,18,19,20] and YFV [21,22,23], mainly through a virtual screening approach. Although different classes of compounds were identified that inhibited DENV, only a handful worked on WNV.…”
Section: Inhibitors Of Viral Targetsmentioning
confidence: 99%